2021
DOI: 10.1111/rec.13492
|View full text |Cite
|
Sign up to set email alerts
|

Predicting optimal habitats of Haloxylon persicum for ecosystem restoration using ensemble ecological niche modeling under climate change in southeast Iran

Abstract: Ecological restoration plays a vital role in the management of degraded ecosystems; nevertheless, the success of restoration plans depends to a large extent on determining optimal habitats for target species' growth and survival. Ecological niche modeling can be used to predict where climate is presently suitable for a particular species used in restoration, and where suitable climates will be located in the future. Here, we used ensemble ecological modeling to identify areas suitable for restoration of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…According to the evaluation metrics, the six single species distribution models of FDA, GBM, RF, MAXENT, GLM, and MARS performed better, followed by GAM, ANN, and CTA models, while the SRE model performed the worst. This is consistent with other results using multiple models to predict species distribution, which shows that the simulation effect of RF is better, while the performance of SRE is the worst [2,32,66]. Some studies have shown that there is some uncertainty in using ROC alone to evaluate the model [67].…”
Section: Ensemble Model Evaluationsupporting
confidence: 90%
See 3 more Smart Citations
“…According to the evaluation metrics, the six single species distribution models of FDA, GBM, RF, MAXENT, GLM, and MARS performed better, followed by GAM, ANN, and CTA models, while the SRE model performed the worst. This is consistent with other results using multiple models to predict species distribution, which shows that the simulation effect of RF is better, while the performance of SRE is the worst [2,32,66]. Some studies have shown that there is some uncertainty in using ROC alone to evaluate the model [67].…”
Section: Ensemble Model Evaluationsupporting
confidence: 90%
“…Most SDMs require species absence data. In this research, we randomly generated pseudo-existence point data at least 3 km between the pseudo-existence points and the existence point data [27,32]. To reduce the predictive uncertainty caused by the randomly generated point position, we generated three sets of pseudo-absence data, and the number of pseudo-existence points in each group was 1500.…”
Section: Environmental Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, choosing the right model for analysis and obtaining an accurate and reasonable distribution of predicted species is difficult because the principles and algorithms of each model are different [33]. To resolve this type of uncertainty, an increasing number of studies employ ensemble modeling approaches that combine predictions from different modeling techniques [34].…”
Section: Why the Ensemble Model?mentioning
confidence: 99%